2019
DOI: 10.1155/2019/3827201
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Multi‐Switching Synchronization of High‐Order Memristor‐Based Hyperchaotic System with Unknown Parameters and Its Application in Secure Communication

Abstract: This article investigates an adaptive multi-switching synchronization for two identical high-order memristor-based hyperchaotic systems with uncertain parameters. Firstly, the dynamic characteristics of two high-order memristor hyperchaotic systems with uncertain parameters are analyzed. Then, an adaptive multi-switching controller is designed to realize the multi-switching synchronization of the two high-order hyperchaotic systems, and the unknown parameters of the systems are identified to their true values.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…A large number of new chaotic systems have been proposed one after another, and their application scopes are more and more extensive [1][2][3][4][5][6][7][8]. With the progress of science and technology, chaos has been applied not only to communication [9][10][11][12], image processing [13][14][15], complex networks [16][17][18][19][20][21], synchronization [22][23][24][25][26][27], electronic circuits [28][29][30], and optimization [31][32][33][34][35] but also to encryption studies [36][37][38][39][40][41]. is is because chaotic signal has good pseudorandom, initial-value sensitive, and long-term unpredictable characteristics, which enhances the confusion and diffusion of encrypted data.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of new chaotic systems have been proposed one after another, and their application scopes are more and more extensive [1][2][3][4][5][6][7][8]. With the progress of science and technology, chaos has been applied not only to communication [9][10][11][12], image processing [13][14][15], complex networks [16][17][18][19][20][21], synchronization [22][23][24][25][26][27], electronic circuits [28][29][30], and optimization [31][32][33][34][35] but also to encryption studies [36][37][38][39][40][41]. is is because chaotic signal has good pseudorandom, initial-value sensitive, and long-term unpredictable characteristics, which enhances the confusion and diffusion of encrypted data.…”
Section: Introductionmentioning
confidence: 99%
“…By increasing the system dimension and incorporating nonlinear terms, the dynamics of a hyperchaotic system become more complex and unpredictable. Compared to traditional chaotic systems, hyperchaotic systems exhibit higher key sensitivity, unpredictability, and pseudo-random properties [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the chaotic system has the characteristics of sensitivity of initial value and complexity of trajectory, so chaos has great potential application in many engineering fields, such as weak signal detection, [1][2][3][4] random number generator, [5,6] secure communication, [7][8][9][10][11][12][13] and image encryption. [14][15][16][17][18][19][20] Furthermore, Lin et al [21,22] studied the influence of electromagnetic radiation on the chaotic characteristics of neural networks, and found that appropriate electromagnetic radiation is helpful to treat some neurological diseases.…”
Section: Introductionmentioning
confidence: 99%